Ineffectiveness of Intermittent Hemodialysis in a Critically Ill COVID-19 Patient: A Case of Persistent Heparin-Induced Hyperkalemia - Yannick M. Nlandu; Yannick M. Engole; Marie-France I. Mboliassa; Théodore-Junior M. Sakaji; Patrick U. Kobo; Patrick M. Boloko; Pally K. Mafuta; Joseph P. Tsangu; Karel Van Echkout; Jean-Pierre M. Kanku; Golan Kalifa; Rodolphe Ahmed; et al. (Case Reports in Nephrology)
Heparin is widely used in the intensive care unit despite the risk of bleeding it can cause. Although it is rarely reported, hyperkalemia is one of the side effects associated with heparin therapy (unfractionated or fractionated heparin). It would be secondary to hypoaldosteronism by blocking the biosynthesis of aldosterone in the adrenal gland and often appears in context of prolonged heparin therapy or inappropriate renin production in elderly, diabetic, and kidney insufficiency patients. We report a case of persistent hyperkalemia in a diabetic COVID-19 patient treated with curative heparin in the context of severe COVID-19.